Real world effectiveness of subcutaneous semaglutide in type 2 diabetes: A retrospective, cohort study (Sema-MiDiab01) - Berra, Cesare C.; Rossi, Maria Chiara; Mirani, Marco; Ceccarelli Ceccarelli, Daniela; Romano, Cristina; Sassi, Lorenza; Peretti, Elena; Favacchio, Giuseppe; Pastore, Ida; Folini, Laura; Graziano, Giusi; Lunati, Maria Elena; et al. (Frontiers in Endocrinology, 2023)
Aim of the present study was to evaluate the real-world impact of once-weekly (OW) subcutaneous semaglutide on different end-points indicative of metabolic control, cardiovascular risk factors, and beta-cell function in type 2 diabetes (T2DM). This was a retrospective, observational study conducted in 5 diabetes clinics in Italy. Changes in HbA1c, fasting blood glucose (FBG), body weight, blood pressure, lipid profile, renal function, and beta-cell function (HOMA-B) during 12 months were evaluated. Overall, 594 patients (97% GLP-1 naïve) were identified (mean age 63.9±9.5 years, 58.7% men, diabetes duration 11.4±8.0 years). After 6 months of treatment with OW semaglutide, HbA1c levels were reduced by 0.90%, FBG by 26 mg/dl, and body weight by 3.43 kg. Systolic blood pressure, total and LDL-cholesterol significantly improved. Benefits were sustained at 12 months. Renal safety was documented. HOMA-B increased from 40.28% to 57.81% after 6 months (p<0.0001). The study highlighted benefits of semaglutide on metabolic control, multiple CV risk factors, and renal safety in the real-world. Semaglutide seems to be an advisable option for preservation of β-cell function and early evidence suggests it might have a role in modifying insulin resistance (HOMA-IR), the pathogenetic basis of prediabetes and T2DM.